2011
DOI: 10.1002/iub.532
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of antibiotic resistance in pathogenic Acinetobacter species

Abstract: SummaryAntibiotic resistance in Acinetobacter spp., particularly Acinetobacter baumannii, is increasing rapidly. A. baumannii possesses two intrinsic b-lactamase genes, in addition to weak permeability and efflux systems, that together confer a natural reduced susceptibility to antibiotics. In addition, numerous acquired mechanisms of resistance have been identified in A. baumannii. The very high genetic plasticity of A. baumannii allows an accumulation of resistance determinants that give rise to multidrug re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
117
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(121 citation statements)
references
References 47 publications
(67 reference statements)
1
117
1
2
Order By: Relevance
“…For example, a retrospective study of ICU-acquired infections in the ICU of the National Cancer Institute of Mexico reported that A. baumannii was the causative agent of 6% of total hospital-acquired infections but disproportionately represented 60% of pneumonia and 25% of bloodstream infections (7). A. baumannii has rapidly evolved into a difficult-to-treat pathogen through acquisition, mostly via integrons and transposons, of multiple drug resistance genes that supplement the already high level of intrinsic drug resistance (8). A recent study analyzing more than 1,300 globally collected bloodstream isolates included over 150 A. baumannii isolates (4).…”
mentioning
confidence: 99%
“…For example, a retrospective study of ICU-acquired infections in the ICU of the National Cancer Institute of Mexico reported that A. baumannii was the causative agent of 6% of total hospital-acquired infections but disproportionately represented 60% of pneumonia and 25% of bloodstream infections (7). A. baumannii has rapidly evolved into a difficult-to-treat pathogen through acquisition, mostly via integrons and transposons, of multiple drug resistance genes that supplement the already high level of intrinsic drug resistance (8). A recent study analyzing more than 1,300 globally collected bloodstream isolates included over 150 A. baumannii isolates (4).…”
mentioning
confidence: 99%
“…An increased expression of the bla OXA-228-like genes was observed in a single isolate, mirroring the ␤-lactam resistance pattern observed and being mediated by promoter changes and not by strong promoters mediated by insertion sequences as shown for the bla OXA-51 gene in A. baumannii (5,22). That finding is different from those related to the overexpression of the intrinsic class D ␤-lactamase genes in A. baumannii, with insertion sequences ISAba1 and ISAba9 located upstream of the bla OXA-51 -like genes and providing strong promoters (5,17).…”
Section: Resultsmentioning
confidence: 75%
“…ESBL genes are often associated with carbapenem and aminoglycoside resistance genes (10). In addition, integrons may contribute to beta-lactamase overproduction and dissemination (11); also, carrying integrons facilitate the spread of resistance genes among bacteria (12).…”
Section: Introductionmentioning
confidence: 99%